Development and Evaluation of a Deep Learning–Based Pulmonary Hypertension Screening Algorithm Using a Digital Stethoscope - Ling Guo; Nivedita Khobragade; Spencer Kieu; Suleman Ilyas; Preston N. Nicely; Emmanuel K. Asiedu; Fabio V. Lima; Caroline Currie; Emileigh Lastowski; Gaurav Choudhary (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Despite the poor outcomes related to the presence of pulmonary hypertension, it often goes undiagnosed in part because of low suspicion and screening tools not being easily accessible such as echocardiography. A new readily available screening tool to identify elevated pulmonary artery systolic pressures is needed to help with the prognosis and timely treatment of underlying causes such as heart failure or pulmonary vascular remodeling. We developed a deep learning–based method that uses phonocardiograms (PCGs) for the detection of elevated pulmonary artery systolic pressure, an indicator of pulmonary hypertension. Methods Approximately 6000 PCG recordings with the corresponding echocardiogram‐based estimated pulmonary artery systolic pressure values, as well as ≈169 000 PCG recordings without associated echocardiograms, were used for training a deep convolutional network to detect pulmonary artery systolic pressures ≥40 mm Hg in a semisupervised manner. Each 15‐second PCG, recorded using a digital stethoscope, was processed to generate 5‐second mel‐spectrograms. An additional labeled data set of 196 patients was used for testing. GradCAM++ was used to visualize high importance segments contributing to the network decision. Results An average area under the receiver operator characteristic curve of 0.79 was obtained across 5 cross‐validation folds. The testing data set gave a sensitivity of 0.71 and a specificity of 0.73, with pulmonic and left subclavicular locations having higher sensitivities. GradCAM++ technique highlighted physiologically meaningful PCG segments in example pulmonary hypertension recordings. Conclusions We demonstrated the feasibility of using digital stethoscopes in conjunction with deep learning algorithms as a low‐cost, noninvasive, and easily accessible screening tool for early detection of pulmonary hypertension.